Are least developed countries sidelined in advanced manufacturing production networks? - Alisa DiCaprio; Sithanonxay Suvannaphakdy (Asian Development Bank Institute (ADBI), 2017)
The fragmentation of production has expanded the geographic reach of even the most high-technology value chains into non-traditional suppliers. It has been suggested that the production of parts for high-technology final products can play an important role in advancing economic development. This is a particularly attractive outcome for poor countries. But due to data constraints, existing analysis is based largely on middle-income economies. In this paper, we seek to address this oversight by using proxy data to explore the position of the Least Developed Countries (LDCs) located in Asia's vibrant regional production hub for electronics and automotive production. Have they also been able to benefit from the fragmentation of the production process? Our examination shows that there has been a surprising amount of LDC trade activity in these sectors over the past decade. In addition, a selected group of LDCs has succeeded in what appears to be successful engagement with these production networks. We discuss the forms of participation we observe and ask whether they might enable countries to attain development outcomes that might otherwise be out of their reach.
Keywords: F14; F15; F23; O24; 330; Asia; LDCs; value chains; electronics; automobiles